Evaluasi Magang Persekolahan Mahasiswa Program Studi Pendidikan Agama Islam - Darodjat Darodjat; Ahmad Sulaeman; Zakiyah Zakiyah; Makhful Makhful; Kusno Kusno (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This is an evaluative study, this research is set at SMP Muhammadiyah 1 Purwokerto and SMA Muhammadiyah 1 Purwokerto, have been accredited with an A predicate, and have carried out collaborative school internship program for undergraduate students of the Islamic Education Department during the coronavirus pandemic continuously. The objectives of this research are: a) the internship evaluation results to improve the quality of student learning on campus in the next period, b) the development of activities in the Merdeka Belajar Kampus Merdeka curriculum, c) the competence of graduates can be improved, d) partners get by the existence of school internship students. The conclusions of this study are: 1) context evaluation is very good (excellent), 2) on the input component, classified as very good; 3) in the process component, the implementation of school internships is in the very good category. However, several indicators of the implementation of the internship show a fairly good condition. Considering that school internships are carried out during a pandemic, so there are students who experience obstacles in developing innovative learning media; 4) on the product component, school internships can achieve good results, which are assessed in an integrated manner.Keywords: School internship evaluation, CIPP modelI